Low Levels of Hydrogen Sulfide in the Blood of Diabetes Patients and Streptozotocin-Treated Rats Causes Vascular Inflammation? - Jain, Sushil K. (Mary Ann Liebert, Inc., 2010)
Hydrogen sulfide (H(2)S) is emerging as a physiological neuromodulator as well as a smooth muscle relaxant. We submit the first evidence that blood H(2)S levels are significantly lower in fasting blood obtained from type 2 diabetes patients compared with age-matched healthy subjects, and in streptozotocin-treated diabetic rats compared with control Sprague–Dawley rats. We further observed that supplementation with H(2)S or an endogenous precursor of H(2)S (l-cysteine) in culture medium prevents IL-8 and MCP-1 secretion in high-glucose–treated human U937 monocytes. These first observations led to the hypothesis that lower blood H(2)S levels may contribute to the vascular inflammation seen in diabetes. Antioxid. Redox Signal. 12, 1333–1338.